Implementation of Pursed Lip Breathing Technique Increases Oxygenation Status and Makes Breathing Patterns More Effective in Children with Bronchial Asthma: Penerapan Pursed Lip Breathing Meningkatkan Status Oksigenasi dan Membuat Pola Napas Efektif Pada Anak Dengan Asma Bronkial - Riyanti, Fina; Nursasmita, Rizqi (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Bronchial asthma is a condition where the respiratory tract experiences narrowing due to hyperactivity to certain stimuli which causes temporary narrowing and asthma can cause non-infectious lung disease, this narrowing can be triggered by various stimuli. Signs and symptoms that appear are wheezing, shortness of breath, coughing, difficulty breathing, especially at night, prolongation of expiratory air flow. One action that nurses can take for children with ineffective breathing patterns is: pursed lip breathing through modified balloon blowing. This study aims to increase oxygenation status and breathing pattern more effective through pursed lip breathing to children with bronchial asthma. The service was carried out by applying it to 2 children who were hospitalized with a medical diagnosis of bronchial asthma. Simulation of pursed lip breathing with modification of blowing up a balloon. Application of pursed lip breathing with modified balloon inflatables can increase oxygenation status and make breathing patterns more effective. The oxygenation status are increases and the breathing patterns more effective. This technique can be applied and taught to families of children with bronchial asthma.